Developing an instrument to assess pedagogical content knowledge for biological socioscientific issues - HAN TOSUNOĞLU, ÇİĞDEM (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
Addressing socioscientific issues (SSIs) in the classroom provides an appropriate context to concentrate on several components of scientific literacy. The purpose of the study was to develop a valid, reliable, instrument to assess teachers' PCK for biological socioscientific issues (PCK-BSSIs). In this paper, two aspects of the research have been described; the framework on which PCK-BSSI is based, and the development, administration, and analysis procedures of the instrument. The PCK-BSSIs will allow re-searchers to explore teachers' understanding of SSIs, how teachers' PCK for BSSIs develops over time, and the relative efficacy of various professional developments. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: Pedagogical content knowledge; Socioscientific issues; Teaching of socioscientific issues; Professional development; SOCIO-SCIENTIFIC ISSUES; SUBJECT-MATTER; TEACHERS PCK; SCIENCE; EDUCATION; CONCEPTUALIZATION; VALIDATION; IMPACT; SKILLS; PLANT